Maize food chain and mycotoxins: A review on occurrence studies. (September 2021) - Leite, Marta; Freitas, Andreia; Silva, Ana Sanches; Barbosa, Jorge; Ramos, Fernando
Abstract: Background: Mycotoxins are secondary metabolites produced by fungal species that colonize cereal crops and, consequently, contaminate them with these toxic compounds, either in the field or in post-harvest commodities. Maize ( Zea mays L.), one of the most prominent crops worldwide, is a great example of infected cultivars with severe impacts mostly affecting farmer and livestock workers, with direct losses in crops, production profitability, animal health and product safety. Scope and approach: This review aims at describing and evaluating published occurrence studies from 2005 to 2020, regarding the identification and quantification of regulated, masked, and emerging mycotoxins throughout the several stages of the complex food chain of maize. An overview of global occurrence surveys and small-scale studies in individual countries is performed, being the use of LC-MS/MS as the analytical approach for characterizing the mycotoxic profile a crucial selection factor. Key findings and conclusions: Deoxynivalenol and zearalenone are the most prevalent mycotoxins encountered at the primary level of the maize chain for both grain-maize and whole maize plants. Maize silage, a major component of dairy feed, is a main source of aflatoxin B1, and, also, of deoxynivalenol and zearalenone. Maize grains for feed or food, have the highest values of fumonisins, and, in certain worldwide regions, of aflatoxins. Emerging mycotoxins are highly present in the overall feed and food chain. Co-contamination patterns were very frequent in all studies, which presents itself as important data to re-evaluate the current legal maximum limits established. Graphical abstract: Image 1 Highlights: ZEA and DON are highly crop and silage-associated mycotoxins. Maize grains for animal and human consumption have the highest content of FBs. Carry-over of ZEA, DON, OTA, and FBs into milk needs further monitoring. Emerging mycotoxins present high contamination levels at all maize chain stages. Co-occurrence of mycotoxins along the maize value chain is very frequent.